Rethinking learning? Challenging and accommodating neoliberal educational agenda in the integration of Forest School into mainstream educational settings. Issue 3 (12th June 2019) - Pimlott‐Wilson, Helena; Coates, Janine
Abstract : A nation's education system plays a key role in future economic competitiveness. Political attention to education has fuelled geographical interest in the role of formal education and informal learning environments in the cultivation of future citizen‐workers. To date, formal and informal learning have largely been considered separately, but this paper responds by critically evaluating the intersections between the two spheres. This agenda is pursued through in‐depth analysis of two state‐funded, mainstream primary schools in the Midlands, UK, which adopt a Forest School programme. Qualitative in nature, the research involved 37 semi‐structured interviews with teachers and children in the Reception class and Year 4 (ages four to five, and eight to nine, respectively). The findings demonstrate that children understand classroom learning to contribute to their future pathways in a credentialised labour market, yet some struggle to frame Forest School activities as educational. Although presented as an antidote to the regimen of the school day, Forest School can thus be justified by some participants in relation to curriculum alignment and the future efficacy of the skills and knowledge acquired. In conclusion, this paper contributes to debates on the intersections of formal and informal education to examine how alternative education can function to counteract the institutionalisation of mainstream settings, while paradoxically developing skills in children that are valued by neoliberal states. More broadly, this furthers debates in geographies of education about what constitutes valuable learning in the primary school setting, and draws attention to the ways innovations might further exclude children currently disadvantaged in the education system. Abstract : This paper contributes to debates on the intersections of formal and informal education to examine how alternative education can function to counteract the institutionalisation of mainstream settings, whilst paradoxically developing skills in children that are valued by neoliberal states. More broadly, this furthers debates in Geographies of Education about what constitutes valuable learning in the primary school setting, and draws attention to the ways innovations might further exclude children currently disadvantaged in the education system.